Women speak out... (Rivista di Studi e Ricerche sulla criminalità organizzata, 2024)
The paper traces some stories of women who, before and after Giuseppa Di Sano, whose testimony against the mafia   – included in the report of Palermo prefect Ermanno Sangiorgi in Palermo on 20 November 1898 –  is reported in the document of History and Memory section, have had the strength to speak out against the mafia.